The Scope of the Banten Provincial Government’s Authority in Population Control Under Indonesia’s Regional Governance Framework - Bambang Heriyanto; Abu Nawas; Muhammad Chotib (UIN Jakarta, 2026)
This study examines the scope of the Banten Provincial Government’s authority in implementing population control policies within Indonesia’s decentralized governance system. The research is grounded in the principle of decentralization as regulated under Law Number 23 of 2014 concerning Regional Government, which establishes the distribution of governmental affairs between the central and regional governments. The study specifically addresses two main issues: first, the authority of the Banten Provincial Government in implementing population control programs; and second, the institutional balance between the National Population and Family Planning Agency (Badan Kependudukan dan Keluarga Berencana Nasional / BKKBN) and the Office of Women Empowerment, Child Protection, Population Control, and Family Planning of Banten Province (DP3AKKB) in implementing population control policies under Law Number 52 of 2009 concerning Population Development and Family Development. This research employs an empirical juridical method to examine the governmental affairs assigned to the Banten Provincial Government in the population control sector and to analyze the coordination between BKKBN and DP3AKKB as the primary institutions responsible for policy implementation. The study uses statutory analysis supported by empirical findings derived from institutional practices and policy implementation. The findings indicate that the authority of the Banten Provincial Government in population control affairs is regulated under Articles 11 and 12 of Law Number 23 of 2014 concerning Regional Government, which also carries financial implications under Law Number 33 of 2004 concerning Fiscal Balance between the Central Government and Regional Governments. Furthermore, the implementation of population control programs by BKKBN and DP3AKKB has not yet achieved optimal balance and effectiveness. This condition arises from the transfer of authority over family planning and population control programs from the central government to regional governments, resulting in policy disparities and variations in implementation among different regions. This study concludes that although decentralization aims to strengthen regional autonomy in population control governance, the shift in authority has created challenges related to institutional coordination, policy harmonization, and program effectiveness. Therefore, stronger intergovernmental coordination and regulatory synchronization are necessary to ensure effective and equitable implementation of population control policies across regions in Indonesia. Keywords: Population Control; Regional Government Authority; Decentralization; Family Development; Regional Autonomy; BKKBN; Public Governance; Indonesia.